Capillary Water Absorption and Chloride Transport Into Mortar Samples: A Finite Element Analysis - Montoya, R.; Nagel, V. (Frontiers in Materials, 2020)
In this work the Richard's equation with proper boundary conditions was solved by the Finite Element Method in order to simulate the capillary water entrance in mortar. On the boundaries subjected to free water, a constant Dirichlet boundary condition was imposed assuming permanent saturation water content, on the insulated boundaries a nil flux of water was fixed. Meanwhile on the boundaries in contact with a controlled external atmosphere, a physicochemical model was used in order to simulate the water evaporation process. Three special sample geometries, with and without cracks, were studied. Findings identified  the initial water content as a very important parameter in the water uptake phenomenon. Once the model for the water entrance was tested with pure water, a governing equation for the chloride transport was coupled with the Richard's equation in order to simulate both the water and chloride transport into simulated mortar samples in contact with sea water. The borders were subjected to different physical conditions for the sake of a better understanding of the role of boundary conditions in the transport of chloride. The governing  equation takes into account the convective effect of the water entrance, the diffusion process and the chloride binding reaction.